Electronegativity-induced charge balancing to boost stability and activity of amorphous electrocatalysts - Zhou, Yao (2022)
Amorphization is an efficient strategy to activate intrinsically inert catalysts. However, the low crystallinity of amorphous catalysts often causes high solubility and poor electrochemical stability in aqueous solution. Here, a different mechanism is developed to simultaneously stabilize and activate the water-soluble amorphous MoSx Oy via a charge-balancing strategy, which is induced by different electronegativity between the co-dopants Rh (2.28) and Sn (1.96). The electron-rich Sn prefers to stabilize the unstable apical O sites in MoSx Oy through charge transfer, which can prevent the H from attacking. Meanwhile, the Rh, as the charge regulator, shifts the main active sites on the basal plane from inert Sn to active apical Rh sites. As a result, the amorphous RhSn-MoSx Oy exhibits drastic enhancement in electrochemical stability (η10 increases only by 12 mV) after 1000 cycles and a distinct activity (η10 : 26 mV and Tafel: 30.8 mV dec-1 ) for the hydrogen evolution reaction in acidic solution. This work paves a route for turning impracticably water-soluble catalysts into treasure and inspires new ideas to design high-performance amorphous electrocatalysts.